Principles of formation of clerical identity in Isidore’s of Seville treatise On ecclesiastical offices - Mikhail Birkin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article studies the notion of the clergy of Isidore of Seville (ca. 560–636). The main source is the treatise “On Ecclesiastical Offi ces”, which was not studied from this point of view before. The article analyses the symbolic meaning of the tonsure, which received its place in canon law through the eff orts of Isidore, as well as his interpretation of the term clerus. By means of intertextual and comparative historical analysis, the article identifi es constituent elements of clergymen’s ethos, namely its relationship with early Christian communities and virginity, which does not completely correlate with celibacy. The main texts have been Octavius by Minucius Felix and On Holy Virginity by St. Augustine. Isidore especially stressed literacy and education among the essential features of the clergy. The author of the articles comes to the conclusion that all these elements are connected by the notion of the sacred status of the clergy, which was a prerequisite for the successful service to God and for the instruction of the fl ock.